Characterization, sources and risk assessment of PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) and nitrated PAHs (NPAHs) in Harbin, a cold city in Northern China - Ma, Lixin; Li, Bo; Liu, Yuping; Sun, Xiazhong; Fu, Donglei; Sun, Shaojing; Thapa, Samit; Geng, Jialu; Qi, Hong; Zhang, Anping; Tian, Chongguo (Journal of cleaner production, 2020)
Inhalation of atmospheric particulates is an significant way for polycyclic aromatic hydrocarbons (PAHs) and substituted PAHs (SPAHs) to enter the human lungs. Some SPAHs are more virulent than parent PAHs. Atmospheric fine particulate matter (PM2.5) samples were obtained at Harbin Institute of Technology (HIT) in Harbin, China. This study provided the first description, source apportionment, and health risk for PM2.5-bound 16 PAHs and 16 nitrated PAHs (NPAHs) in cold regions of China. On average, the PM2.5, PM2.5-bound PAHs and NPAHs concentrations were 80.8 μg/m3, 86.9 ng/m³ and 5.48 ng/m³. Significant increases in PM2.5 (274 μg/m³) and PM2.5-bound NPAHs (24.7 ng/m³) concentrations were measured during the straw burning in autumn, while the concentration of PM2.5-bound PAHs (215 ng/m³) increased obviously in winter. Source apportionment showed that the main source of PAHs was combustion, while besides direct emissions, about 20% of NPAHs came from the secondary formation. Controlling coal combustion and biomass burning might be an effective measure to improve air quality during the heating period in Harbin. The influence of meteorological conditions on PAHs and NPAHs concentration indicated that pollutants were more susceptible to meteorological conditions during the heating period than during the non-heating period, especially for PAHs. The health risk analysis indicated that the highest health risk caused by exposure to the PM2.5-bound PAHs and NPAHs was in winter, and this was inconsistent with the trend of PM2.5 pollution. Cancer risk assessments demonstrated the potential cancer risk at this PAHs and NPAHs concentration level. [Display omitted] •The characteristics of PM2.5-bound PAHs and nitro-PAHs were studied in cold regions of China.•The concentrations of PAHs and nitro-PAHs were susceptible to meteorological conditions during heating season.•Controlling coal combustion and biomass combustion is important to improve air quality during heating period.•There is a potential cancer risk due to exposure to these levels of PAHs and nitro-PAHs.